ChemInform Abstract: Lewis Acid Catalyzed Regioselective Hydroheteroarylation of Pentafulvenes. Issue 29 (29th June 2016) - Chand, S. Sarath; Gopalan, Greeshma; Santhini, P. V.; Preethanuj, P.; John, Jubi; Harakat, Dominique; Jaroschik, Florian; Radhakrishnan, K. V.
Abstract: The catalytic regioselective nucleophilic addition of nitrogen heterocycles to Lewis acid activated pentafulvenes is investigated.